The Relationship between Transformational Leadership and Employees’ Creativity in the Jordanian Banking Sector - Suifan, Taghrid S.; Al-Janini, Marwa (International Review of Management and Marketing, 2017)
This study aims to examine the relationship between transformational leadership and employees’ creativity in the Jordanian banking sector. Three hundred and 69 questionnaires were distributed to the employees in different banks. The data were tested using multiple regression to determine whether the four dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration have a significant relationship with employees’ creativity. The findings showed that there is a positive relationship between transformational leadership and employees’ creativity. However, the dimensions of inspirational motivation and intellectual stimulation have been shown not to have a significant relationship with employees’ creativity. Keywords: transformational leadership, employees’ creativity JEL Classficiations: G2, L2